226k views
1 vote
The function h is defined as h (x) = 5x² – 3.
Find h(x+1).

1 Answer

2 votes

Answer:

h(x + 1) = 5x² + 10x + 2

Explanation:

Step 1: Write out function

h(x) = 5x² - 3

Step 2: Plug in x + 1 for x

h(x + 1) = 5(x + 1)² - 3

Step 3: Expand

h(x + 1) = 5(x² + 2x + 1) - 3

Step 4: Distribute

h(x + 1) = 5x² + 10x + 5 - 3

Step 5: Combine like terms

h(x + 1) = 5x² + 10x + 2

User Nick Bauer
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.